Low repetition rate, passively modelocked Ti:Sapphire oscillator - Kardaś, Tomasz Michał; Wasylczyk, Piotr; Gadomski, Wojciech (Photonics Letters of Poland, 2009)
We present two configurations of low repetition rate Ti:Sapphire femtosecond oscillators with the Herriott cell. Pulse energies of 50 nJ at 13.6 MHz and 40 nJ at the 5.4 MHz repetition rate were achieved. We discuss Herriott cell design as well as the details of laser construction. Full Text: PDF References: D. E. Spence, P. N. Kean, W. Sibbett,"60-fsec pulse generation from a self-mode-locked Ti:sapphire laser", Opt. Lett. 16, 42, (1991)[CrossRef] A. Bartels, D. Heinecke, S. A. Diddams,"Passively mode-locked 10 GHz femtosecond Ti:sapphire laser", Opt. Lett. 33, 1905, (2008)[CrossRef] T. M. Fortier, A. Bartels, S. A. Diddams,"Octave-spanning Ti:sapphire laser with a repetition rate >1 GHz for optical frequency measurements and comparisons", Opt. Lett 31, 1011, (2006)[CrossRef] S. Dewald, T. Lang, C. D. Schröter, R. Moshammer, J. Ullrich, M. Siegel, U. Morgner,"Ionization of noble gases with pulses directly from a laser oscillator", [CrossRef] A. Killi, A. Steinmann, J. Dörring, U. Morgner, M. J. Lederer, D. Kopf, C. Fallnich,"High-peak-power pulses from a cavity-dumped Yb:KY(WO4)2 oscillator", Opt. Lett. 30, 1891, (2005)[CrossRef] S. H. Cho, F. X. Kärtner, U. Morgner, E. P. Ippen, J. G. Fujimoto, J. E. Cunningham, W. H. Knox,"Generation of 90-nJ pulses with a 4-MHz repetition-rate Kerr-lens mode-locked Ti:Al2O3 laser operating with net positive and negative intracavity dispersion", Opt. Lett. 26, 560, (2001)[CrossRef] A. Fernandez, T. Fuji, A. Poppe, A. Fürbach, F. Krausz, A. Apolonski,"Chirped-pulse oscillators: a route to high-power femtosecond pulses without external amplification", Opt. Lett. 29, 1366, (2004)[CrossRef] S. H. Cho, B. E. Bouma, E. P. Ippen, J. G. Fujimoto,"Low-repetition-rate high-peak-power Kerr-lens mode-locked TiAl2O3 laser with a multiple-pass cavityLow-repetition-rate high-peak-power Kerr-lens mode-locked TiAl2O3 laser with a multiple-pass cavity", Opt. Lett. 24, 1998, (1999)[CrossRef] A. F. González, "Chirped Pulse Oscillators: Generating microjoule femtosecond pulses at megahertz repetition rate (PhD thesis, München 2007)" A. M. Kowalevicz, A. Sennaroglu, A. Tucay Zare, J. G. Fujimoto,"Design principles of q-preserving multipass-cavity femtosecond lasers", J. Opt. Soc. Am. B 23, 760, (2006)[CrossRef] A. Sennaroglu, J. G. Fujimoto,"Design criteria for Herriott-type multi-pass cavities for ultrashort pulse lasers", Opt. Express 11, 1106, (2003)[CrossRef] S. M. Kelly,"Characteristic sideband instability of periodically amplified average soliton", Electron. Lett 28, 806, (1992)[CrossRef]